INVESTIGATION ON THE PHYSICAL PARAMETERS OF ENVIRONMENT AND THEIR IMPACT ON COTTON CROP PRODUCTION IN THE SOUTHERN PUNJAB, PAKISTAN - Makhdum, Muhammad Iqbal; Malik, Muhammad Nawaz; Ahmad, Fiaz; Chaudhry, Fazal Ilahi; Shabab-ud-Din, (Journal of Research (Science), 2001)
Some physical parameters of the environment and their influence on cotton crop production were studied at Central Cotton Research Institute, Multan (300 12′N,710 28′ E, alt.123m). The results showed that highest rain expectation will be during the month of July and August considering 99 percent confidence intervals for a 10-year mean rainfall. This gives a strong support to the standard recommendation of ending the sowing of cotton by first weak of June to avoid replanting of crop. The modified constants of Penman provide best estimates for potential evapotranspiration, total incoming short wave radiation and net solar radiation. The potential evapotranspiration (Et) is an important component of environment to calculate crop evapotranspiration (ET) to measure crop wateruse at the location.